2006
DOI: 10.1111/j.1440-1827.2006.01995.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell hypothesis in thyroid cancer

Abstract: There is increasing evidence that many types of cancer contain their own stem cells: cancer stem cells, which are characterized by their self-renewing capacity and differentiation ability. Cancer could be regarded as an abnormal organ initiated by cancer stem cells, and cancer stem cells might play a decisive role in tumor initiation and progression. Dysregulation of stem cell self-renewal is a likely requirement for the development of cancer, and stem cells seem more likely to be the transformed target cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…Due to their pluripotency and undifferentiated state, they are widely believed to be involved in the pathogenesis of tumors (15,16). This concept has also recently been hypothesized for thyroid carcinogenesis (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their pluripotency and undifferentiated state, they are widely believed to be involved in the pathogenesis of tumors (15,16). This concept has also recently been hypothesized for thyroid carcinogenesis (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular alterations that cause the formation of these benign neoplasias are largely unknown (4). Recently stem cells have been hypothesized to be a source of malignant tumors including thyroid carcinomas (17,18). In the case of colon tumors, the concept of stem cell transformation has also been extended to adenomas (41).…”
Section: Discussionmentioning
confidence: 99%
“…Follicular and papillary carcinomas, which are well-differentiated, could arise from bi-potential stem cells. Meduallary carcinoma, another well-differentiated cancer, could originate from progenitor C cells (Zhang et al 2006). Although the discovery of stem cell markers in the thyroid gland indicates the potential for the existence of thyroid cancer stem cells, the identification of these cells could prove to be quite difficult due to the extremely low lifetime turnover in the thyroid gland.…”
Section: Cellular Origin Of Thyroid Cancer Stem Cellsmentioning
confidence: 99%
“…In particular, the CD44 C CD24 /low lineage populations can reconstitute tumors that are made up of a heterogeneous population of cells similar to that from which they were obtained. Subsequently, Zhang et al (2006) presented a model for the origin of the four types of thyroid carcinomas based on their differentiation levels. Anaplastic cancer could form directly from a stem cell because it is poorly differentiated.…”
Section: Cellular Origin Of Thyroid Cancer Stem Cellsmentioning
confidence: 99%
“…Recent studies have reported the presence of cancer stem cells in several types of cancer, for example, leukemia [1][2][3], brain [4][5][6], melanoma [7][8][9][10][11][12][13][14][15][16], thyroid cancer [17], and breast cancer [18,19].…”
Section: Introductionmentioning
confidence: 99%